Opiate bioneutralization and its effects on hypophysial gonadotrophins in cycling Murrah buffaloes - CHANDRASEKHAR, T; MADAN, M L (The Indian Journal of Animal Sciences, 2013)
The effects of opiate bioneutralization on circulating luteinizing and follicle stimulating hormones were studied during luteal phase of 6 cycling Murrah buffaloes using an antiopiate naloxone. Saline was infused into the animals through the jugular vein for 4 hr @ 0.66 ml/min on day 11 of the cycle, and naloxont!hydrochloride (1.5 mg/ kg body wt.) dissolved in saline was infused at the same rate on day 14 of the cycle. Naloxone treatment increased LH levels significantly (P< 0.01) over the saline treatment during the infusion. Mean of LH pulses though high in the naloxone treatment (3.16/4 hr) was not significantly different (rom the saline treatment (2.5/4 hr). But mean magnitude showed a significant difference in naloxone treatment (2.07Â±0.09 ng/ml) compared to the saline treatment (1.33Â±0.05 ng/ml). However. LH in post-infusion samples collected at hourly interval for 4 hr did not show any significant difference over the levels in the saline treatment. FSH levels did not show any significant difference between treatments. The above results showed that naloxone is a short acting anti opiate that can increase LH levels for short periods in animals primed with progesterone.